Corporate Governance: Evidence from Firms Strategic Emphasis - Majdi Anwar Quttainah (Journal of International Conference Proceedings (JICP), 2019)
A firm’s ability to maintain competitiveness, comparative advantage, and long-term productivity growth depends crucially on its Strategic Emphasis (hereinafter; SE). By SE we mean the interaction between firms’ Value Creation and Value Appropriation activities. While Value Creation is based on innovating, producing and delivering products to the market, in contrast, Value Appropriation can be thought of as the extraction of profits by capitalizing on innovative and productive activities (Mizik & Jacobson, 2002). Being able to determine the SE of a firm, is an important factor in understanding the current nature of the firm, and where it is heading, based on the trade-off’s decision embedded within its SE. Despite its importance, very little is known about the role of Corporate Governance in strategic emphasis and the combined effect on firm performance. In this paper, we seek to fill this gap in the literature by providing a comprehensive analysis and new empirical evidence on the relations between CG as represented by the market for corporate control, a firm’s SE, and firm performance. We focus on market for corporate control because, as Mizik and Jacobson (2003) points out, a firm’s internal and external environments are key determinants of Value Creation and the value appropriation. Jensen and Meckling (1979) further demonstrated that the market for corporate control is one of the most important components of a firm’s external environment. Market for corporate control refers to a takeover market where the underperforming or undervalued firms become attractive takeover targets. Hostile takeovers are regarded as one of the harshest forms of managerial discipline and usually result in a subsequent loss of wealth for these managers (Heath & Norman, 2004). As a result of the threat of hostile takeovers, publicly traded firms may be more willing to act in the interest of shareholders. This happens when the internal governance mechanism (board of directors) fails. When firms perform poorly, it often indicates that there was poor internal governance and therefore external governance control takes over. The market for corporate control allows shareholders to discipline the management of the firm. Shareholders usually favor a high-performing firm that can maintain its competitiveness, comparative advantage, and long-term productivity growth and are more likely to exercise their influence over the management of firms that do not demonstrate these characteristics (Anabtawi & Stout, 2007). Although capital markets pressure top managers to focus on short-term projects and neglect innovation (Holmstrom, 1989), innovation is a major driver of economic growth (Solow, 1957; Romer,1990). Thus, this paper attempts to answer the questions: (1) To what extent does the market for corporate control affect a firm’s SE decision? (2) Given that the market for corporate control pressures managers, to what extent does it impact the firm’s allocated resources between VC and value appropriation? We hypothesize that the market for corporate control determines and impacts the intensity of the se increase whether on value appropriation or VC and what influence this direction. The rest of this paper is organized as follows. Section 2 provides related theory development, literature review and hypotheses development. Section 3 describes our data and variable construction. Section 4 describes the methodology. Section 5 discusses our main results, endogeneity concerns and robustness checks. Section 6 provides recommendations for further research and conclusion.